Multi-level analysis of environmental disclosure by Brazilian and German firms - Maia Amorim, Karla Vanessa Nogueira; Oliveira, Marcelle Colares; Rodrigues Júnior, Manuel Salgueiro (Review of Business Management, 2021)
Purpose: The influence of macro-, meso-, and micro-level factors on corporate environmental disclosure was evaluated for a sample of German and Brazilian firms belonging to environmentally sensitive sectors. Theoretical framework: The macro-level analysis was based on the national business system approach (Whitley, 1999), the meso-level analysis was based on business sector (Campbell, 2007; Ederington & Minier, 2003), and the micro-level analysis was based on endogenous corporate variables (Sánchez, Domínguez, & Álvarez, 2011; Waddock & Graves, 1997). Methods: Data covering the 2014-2016 period were retrieved from sustainability and financial reports issued by firms in six sectors (aviation, energy, timber, paper, chemicals, and textiles) and subjected to panel data analysis and hierarchical linear modeling. Results: Our results confirm the hypothesized association between environmental disclosure and national culture. Business sector was also a significant factor, but the strongest determinants were firm size and profitability. Practical and social implications: The endogenous (micro-level) variables displayed the greatest explanatory power for environmental disclosure in both countries. Investigators in this field are therefore advised to direct more attention to factors at this level. Contributions: Hierarchical linear modeling increased our ability to evaluate the factors influencing corporate environmental practices.